Transition metal-doped Sb2Te3 single crystals - Lošťák, Petr; Drašar, Čestmír; Uher, Ctirad (Univerzita Pardubice, 2005)
In this review paper we present and discuss results of extensive studies made on single crystals of the tetradynamite-type compound Sb2Te3 doped with the transition metal elements. We focus on the transport and magnetic measurements made ower the temperature range 2 - 300K and show that the Sb2-xMexTe3 (Me=Ti, Mn, V, and Cr) compounds reveal a variety of interesting physical properties. Among them is the existence of a long-range magnetic order that characterizes some of the compounds as novel diluted magnetic semiconductors.
Keywords: monokrystaly; Sb2Te3; přechodová charakteristika; polovodiče; tetradymitová struktura; Hallova konstanta; Seebeckův koeficient